Recombinant Human Interleukin-2 Corrects NK Cell Phenotype and Functional Activity in Patients with Post-COVID Syndrome - Andrei A. Savchenko; Igor V. Kudryavtsev; Dmitry V. Isakov; Ivan S. Sadowski; Vasily D. Belenyuk; Alexandr G. Borisov (MDPI AG, 2023)
Post-COVID syndrome develops in 10-20% of people who have recovered from COVID-19 and it is characterized by impaired function of the nervous, cardiovascular, and immune systems. Previously, it was found that patients who recovered from infection with the SARS-CoV-2 virus had a decrease in the number and functional activity of NK cells. The aim of the study was to assess the effectiveness of recombinant human IL-2 (rhIL-2) administered to correct NK cell phenotype and functional activity in patients with post-COVID syndrome. Patients were examined after 3 months for acute COVID-19 of varying severity. The phenotype of the peripheral blood NK cells was studied by flow cytometry. It was found that disturbances in the cell subset composition in patients with post-COVID syndrome were characterized by low levels of mature (p = 0.001) and cytotoxic NK cells (p = 0.013), with increased release of immature NK cells (p = 0.023). Functional deficiency of NK cells in post-COVID syndrome was characterized by lowered cytotoxic activity due to the decreased count of CD57+ (p = 0.001) and CD8+ (p < 0.001) NK cells. In the treatment of patients with post-COVID syndrome with recombinant IL-2, peripheral blood NK cell count and functional potential were restored. In general, the effectiveness of using rhIL-2 in treatment of post-COVID syndrome has been proven in patients with low levels of NK cells.